A case of polycystic kidney disease infection caused by Brucella: report and literature review - Peng Su; Peng Su; Guotu Du; Ying Yang; Hong Zheng; Neng Zhang (Frontiers in Medicine)
Polycystic kidney disease (PKD) is a common genetic disorder characterized by the progressive development of multiple renal cysts. While cyst infections in PKD are typically caused by common gut flora, infections due to atypical zoonotic pathogens like Brucella are exceedingly rare. We present a unique case of a 40-year-old male patient with PKD who developed a renal cyst infection caused by Brucella following exposure to livestock. Despite initial negative urine cultures, blood cultures confirmed the diagnosis of Brucella infection. The patient was successfully treated with a combination of doxycycline and rifampin. This case underscores the importance of considering zoonotic pathogens in patients with PKD and a history of livestock contact. It also highlights the critical role of early diagnosis and targeted antibiotic therapy in managing such rare infections. Additionally, this study provides a comprehensive review of brucellosis, covering its epidemiology, pathogenesis, clinical manifestations, diagnosis, and treatment strategies.